Robson Ten Group Classification System and Fetal Distress as the Indication for Caesarean Section - Nosheen Bano, Nazia Tufail, Saima Ali, Nosheen Wahab Salman, Nosheen Ghafoor, Ayesha Naeem, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The marked increase in the rates of CS has not only raises the challenges for the medical professional but also became a debatable issues for many gynecologists. In order to explain the increasing rates of CS it is necessary to identify which group of women is more frequently undergoing CS. Objective: The study aimed to evaluate the role the fetal distress and Robson ten group classification play for the indication of caesarean section. Study design: It is a retrospective study conducted at Khawaja Muhammad Safdar Medical College, Allama Iqbal Memorial Teaching Hospital Sialkot, from January 2022 to June 2022. Material and Methods: 5787 women were admitted in tertiary care unit for delivery. Among these 2031 went through caesarean and the remaining delivered normally. Most of the population was included in group 1 and 5, where 501 and 535 individuals were present. Results: The group having the most contribution towards CS was group 5. And the group showing least contribution towards CS was group no.10. Group 5 also showed high contribution towards CS. The evaluation was carried out for 205 patients, the mean age of the patients was 26 years in this study. Most of the patients belonged to gestation week greater than 36 weeks. Conclusion: The group that has low risk had more chances to contribute to the CS rate. The indication for CS was most of the time fetal distress which was seen at the time patients were admitted in hospital. Keywords: Caesarean section and fetal distress.